(untitled) (Revista Brasileira Multidisciplinar, 2024)
Psychotropics are substances that will act on the Central Nervous System, where they will cause changes in behavior and mood in the user. With regard to benzodiazepines (BZDs), these are indicated as the first treatment option for patients who experience anxiety and/or insomnia. Despite being safe and highly efficient drugs, their long-term use is not recommended because it can generate adverse effects such as cognitive, physical, psychomotor effects, tolerance and even generate high dependence on this substance. Therefore, this research aimed to evaluate the use of benzodiazepines in the SUS primary care service in the Municipality of Massaranduba – PB. The research was conducted in a basic pharmacy in that municipality, using the pharmacy system and list B1 prescriptions from June 2022 to June 2023 as a source of information, in order to draw up a profile of the use of BZDs. Regarding the results, there was a prevalence of females in the BZDs prescriptions analyzed, with clonazepam 2 mg being the most prescribed medication. It was observed that 32.3% of patients treated used this medication, exceeding the period of use recommended in the literature. Although scientific findings indicate that diazepam should not be combined with amitriptyline or fluoxetine, we still found a percentage of 11% of prescriptions with this association.